Peran Orang Tua dan Sekolah dalam Pencegahan Bullying/Perundungan Untuk Mencapai Poin 4 SDGs (Pendidikan Berkualitas) di Desa Lubuk Garam Provinsi Riau - Nizmi, Yusnarida Eka; Hunaufalkhair, Mhd Urfa; Sulfita, Nadya; Nurlela, Novlian Ade; Afrizal, Awie; Syamsabil, Fitrah Ahmad; Guzandi, Hamidah; Gusniati, Gusniati; Nabila, Sherla Salsa; Siregar, Natasya Awaliyah; Rifani, Rahmat; Mahesa, I Gede Rakha; Simbolon, Arga (Unri Conference Series: Community Engagement, 2024)
Bullying is a challenge in achieving the Sustainable Development Goals (SDGs) point 4 by 2030, especially at SDN 12 Siak Kecil. Bullying has a significant impact on a child's psychological and academic achievement. This paper aims to describe how parents and schools can play a role in preventing bullying in Lubuk Garam Village, Riau Province. Parents have an important role in instilling positive values in their children's upbringing, while the school environment plays a role in shaping children's character during the academic achievement process. Data collection was carried out through interviews and education related to bullying prevention to map the actual role of parents and schools, and analyzing how bullying behavior becomes a crucial problem in achieving quality education. The method used is a qualitative approach. Based on educational activities as well as the results of surveys and interviews, most students admitted to having committed acts of bullying, which proves that there is a lack of role of parents and schools in tackling the problem. This paper shows that the role of parents and schools still needs to be optimized, so that quality education without bullying can be present as a condition that is targeted in achieving SDGs point 4.